Exploration of economic and environmental impacts of sustainable diversification in the eastern IGP of India - Choudhary, K.M.; Kalvania, K.C.; Ali, Shahid; Sinha, Pooja; Kumar, Sanjeev; Jat, R.K.; Bijarniya, Deepak; Krupnik, Timothy J.; Gathala, Mahesh K. (TAFSSA, 2024)
Challenges to the agricultural systems in the Eastern Indo-Gangetic Plains (EIGP) include low crop productivity correlated with the region’s increased poverty, farmers’ low investment capability and aversion to risk, and increasing energy and input costs, in addition to climatic variability. The EIGP is one of the most vulnerable regions to climate change because of terminal heat in summers, frequent droughts and flood risks, and increasingly erratic monsoon rainfall behavior in recent decades. This research brief presents the findings from on-farm participatory approach research trials focused on the climate-resilient and profitable alternative crop diversification options over to the dominating existing cropping systems. These on-farm research trials were conducted by the Transforming Agrifood Systems in South Asia (TAFSSA) Initiative with the partnership of CGIAR Institutes, JEEViKA, and the Department of Agriculture in Nalanda district of Bihar, India.